Phenological changes in North Atlantic right whale habitat use in Massachusetts Bay. (15th November 2019) - Charif, Russell A.; Shiu, Yu; Muirhead, Charles A.; Clark, Christopher W.; Parks, Susan E.; Rice, Aaron N.
Abstract: The North Atlantic right whale ( Eubalaena glacialis ) is one of the world's most highly endangered baleen whales, with approximately 400–450 individuals remaining. Massachusetts Bay (MB) and Cape Cod Bay (CCB) together comprise one of seven areas in the Gulf of Maine where right whales seasonally congregate. Here, we report on acoustically detected presence of right whales in MB over a nearly 6 year period, July 2007–April 2013, a time of both rapid ocean warming throughout the Gulf of Maine and apparent changes in right whale migratory dynamics. We applied an automated detection algorithm to assess hourly presence of right whale "up‐calls" in recordings from a 19‐channel acoustic array covering approximately 4, 000 km 2 in MB. Over the survey, up‐calls were detected in 95% of 8 day periods. In each year, as expected, we observed a "peak season" of elevated up‐call detections in late winter and early spring corresponding to the season when right whales congregate to feed in CCB. However, we also saw an increase in right whale occurrence during time periods thought to be part of the "off‐season." With the exception of 2009–2010, when acoustic presence was unusually low, the mean percent of hours in which up‐calls were detected increased every year, both during the peak season (from 38% in 2008 to 70% in 2012), and during the summer–fall season (from 2% in 2007 to 13% in 2012). Over the entire study, the peak season start date varied between 17 January and 26 February. Changes in right whale phenology in MB likely reflect broadscale changes in habitat use in other areas within the species range. This study demonstrates the value of continuous long‐term survey datasets to detect and quantify shifts in cetacean habitat use as environmental conditions change and the long‐term continued survival of right whales remains uncertain. Abstract : Year‐round acoustic monitoring of North Atlantic right whale (NARW) presence in Massachusetts Bay (MB) over nearly 6 years revealed that: (a) NARWs were present in 95% of 261 eight day periods; (b) During the winter–spring, NARW presence nearly doubled over the duration of the study; (c) During the summer–fall, NARW presence increased by a factor >6 over the duration of the study; (d) The increasing use of the MB area occurred even as the overall NARW population declined, reflecting range‐wide changes in habitat use; (e) NARW phenology was different between 2007–2010 compared to 2010–2013.